Pemanfaatan Fitur TikTok Affiliate sebagai Media Monetisasi bagi Kreator Beauty @Sheylanada untuk Pendapatan Digital - Naura Vania Ramadhani; Bayu Suriaatmaja Suwanda (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the utilization of TikTok Affiliate features as a monetization medium by beauty content creators, particularly on the account @sheylanada. This research employs a qualitative approach with a descriptive method, using data collection techniques such as observation, interviews, and documentation. The subjects consist of one key informant and three supporting informants who actively use TikTok Affiliate. The results indicate that TikTok Affiliate is effective as an additional source of income in the digital era, supported by marketing communication strategies based on the AIDA concept (Attention, Interest, Desire, Action) and content marketing theory. Creators utilize various features such as sound, hashtags, shopping links, and audience interaction to increase engagement and encourage purchasing decisions. Furthermore, honest product reviews, content consistency, and soft selling approaches play an important role in building audience trust. TikTok Affiliate can be considered a potential monetization strategy for beauty content creators.